Application of hybrid model fuzzy AHP - VIKOR in selection of the most efficient procedure for rectification of the optical sight of the long-range rifle - Radovanovic, Marko; Ranđelović, Aca; Jokić, Željko (Decision Making: Applications in Management and Engineering, 2020)
The paper presents a decision support model when choosing the most efficient rectification procedure of the optical sight of the long - range rifle. The model is based on the fuzzy AHP method and the VIKOR method. Using the fuzzy AHP method, coefficient values of the criteria were defined. Fuzzification of the AHP method was performed by combining data obtained from experts - comparison of criteria in pairs and the degree of confidence in the comparison. Using the VIKOR method, the best alternative was selected. Through the paper, the criteria that condition this choice are elaborated and the application of the method in a specific situation is presented. Also, the paper presents the sensitivity analysis of the developed model.